2019
DOI: 10.21614/chirurgia.114.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anastomoses in Right Hemicolectomy for Colon Cancer

Abstract: Introducere: Cancerul colorectal este unul dintre cele mai frecvent întâlnite tumori maligne ale sistemului digestiv, incidenţa acestei boli crude crescând constant. Materiale şi Metode: 236 de pacienţi diagnosticaţi cu cancer de colon drept au fost revizuiţi retrospectiv. Pentru toţi pacienţii incluşi în acest studiu, hemicolectomie dreaptă sau hemicolectomie dreaptă extinsă cu anastomoză ileo-colonică a fost efectuată. Pacienţii au fost împărţiţi în două grupuri: grupul de studiu incluzând pacienţi care au d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
1
6
0
1
Order By: Relevance
“…In radical surgery for right hemicolectomy, anastomoses of the ileum are various, and lateral anastomosis is common [ 9 , 10 ]. After resection when performing right hemicolectomy, different anastomoses will affect anastomotic blood flow and tension and become a risk factor for postoperative anastomotic leakage [ 11 ]. Because the anastomosis is located at the level of the transverse colon in the upper abdomen, if anastomotic leakage occurs, severe infection may occur in the entire abdominal cavity and intestinal adhesions, intestinal obstruction, and other comorbidities may likely develop, which may even lead to perioperative death in serious cases.…”
Section: Introductionmentioning
confidence: 99%
“…In radical surgery for right hemicolectomy, anastomoses of the ileum are various, and lateral anastomosis is common [ 9 , 10 ]. After resection when performing right hemicolectomy, different anastomoses will affect anastomotic blood flow and tension and become a risk factor for postoperative anastomotic leakage [ 11 ]. Because the anastomosis is located at the level of the transverse colon in the upper abdomen, if anastomotic leakage occurs, severe infection may occur in the entire abdominal cavity and intestinal adhesions, intestinal obstruction, and other comorbidities may likely develop, which may even lead to perioperative death in serious cases.…”
Section: Introductionmentioning
confidence: 99%
“…The study also confirmed better short-term outcomes including shorter hospital stay and reduction of postoperative pain. [ 20 ] Results of another study proved that in right colon tumors, SSA anastomotic technique should be used, being linked with the lowest chances of anastomotic leakage, also being considered with high probability a protective factor in the development of the fistula [ 4 ] . On the contrary, our results show, that SSA is associated with higher occurrence of anastomotic leakage in comparison to other anastomotic types.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] There are different types of ileocolonic anastomosis such as end-to-end anastomosis (EEA), side-to-side anastomosis (SSA), end-to-side anastomosis (ESA) and side-to-end anastomosis (SEA). [ 4 , 5 ] Due to disparity in diameters of colon and ileum, postoperative anastomotic complications are quite common. [ 6 ] Choice of the optimum variant of the anastomosis in RH depends on the understanding of pathophysiological consequences of either intestinal anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage is associated with mortality, short-and long-term morbidity, a potentially increased risk of recurrence, and poor prognosis [1,2]. The anastomotic leakage rate after right-sided colectomy is reported to range from 1.7 to 12% [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, including the host genetic profile, gut microbiome, inflammation, and other immune responses, have been reported to influence the occurrence of anastomotic leakage [1]. Risk factors for anastomotic leakage after right-sided colectomy include age, male sex, body mass index (BMI), diabetes, weight loss > 10%, American Society of Anesthesiologists Physical Status (ASA-PS), chronic obstructive pulmonary disease (COPD), smoking, arterial hypertension, ascites, peripheral vein disease, low protein or albumin (Alb) level, low sodium level, high CRP level, emergency surgery, long operation time, perioperative transfusion, stapled anastomosis, and delayed bowel motility [4,[7][8][9][10][11][12]. The ability to predict the risks of anastomotic leakage, preoperatively or immediately after surgery, would benefit patients scheduled to undergo elective right-sided colectomy.…”
Section: Introductionmentioning
confidence: 99%